Evaluation of orthodontic treatment results among patients treated at the University of the Philippines' graduate program in orthodontics from 1989 to 2003 - Maranon, Marie Joanne Susana R.
The purpose of this study was to evaluate the overall quality of orthodontic treatment at the University of the Philippines' Graduate Program in Orthodontics. Sixty-three post-treatment and nineteen post-retention dental casts and panoramic radiographs were assessed using the American Board of Orthodontics' (ABO) Objective Grading System (ABO Index or ABOI). Only 22.2% of the orthodontic cases examined met or exceed the ABOI standards upon completion of the orthodontic treatment. Furthermore, only one out of the 19 cases evaluated at post-retention exhibited an acceptable ABO score. Post-treatment results showed that the interproximal contacts had the highest average score (58.5 +/- 1.830) out of all the eight (8) ABOI dental criteria and this continued to improve at T3 (59.5 +/- 0.841). The root angulations (58.5 out of 64 points) and buccolingual inclination (36.1 out of 40 points) also elicited high average scores. In contrast, overjet (24.7 +/- 3.885) received the lowest average score and this continued to worsen upon recall (22.5 +/- 3.642.) The average scores of the alignment and root angulations significantly deteriorated at post-retention time point. Although no other statistically differences were observed, it was observed that the mean values for the marginal ridges, buccolingual inclination, occlusal relationships and interproximal contacts generally improved with the passage of time. However, the opposite trend was seen for the mean values of the occlusal contact and overjet. Cephalometric radiographs obtained prior to treatment (T1), at the end of treatment (T2) and post-retention (T3) were assessed for changes in the dental skeletal and soft tissue linear and angular measurements were utilized to quantitate the treatment effects and to assess if changes still occur with the passage of time. Maxillary denture base continued to lengthen from T1 (64.8 +/- 6.087 mm.) through T3 (66.9 +/- 5891 mm.). There was no apparent skeletal change anteroposteriorly. Instead most of the perioral changes seen were due to dental effects. The anteposterior and axial inclination of the upper and lower incisors improved a the end of treatment as evidenced by the retraction and upright position of the anterior teeth. However, there was a tendency for these teeth to move back toward their pretreatment values with time after completion of the orthodontic treatment. Likewise, there was a continued increase in the height of the lower one-third of the fact from T1 through T3. Protrusion of the upper and lower lips, as well as nasal development continued both during treatment and long-term.
Vita.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila
Keywords: Orthodontics